Chronic respiratory morbidity in the Bhopal gas disaster cohorts: a time-trend analysis of cross-sectional data (1986–2016). (September 2020) - De, S.; Shanmugasundaram, D.; Singh, S.; Banerjee, N.; Soni, K.K.; Galgalekar, R.
Abstract: Objectives: In 1984, nearly 500, 000 inhabitants of Bhopal city, India, were exposed to toxic gases that leaked from a nearby pesticide manufacturing plant. In 1985, four cohorts were established to assess the long-term health impact of exposure, namely, mild, moderate, severely exposed and unexposed groups. The self-reported morbidity data of these cohorts were collected by follow-up cross-sectional surveys at regular intervals over the last 35 years. The present study aimed to analyse the long-term trend of chronic (duration of symptoms >3 months) respiratory morbidity in the four cohorts, stratified by age groups. Study design: The design of this study is a longitudinal analysis of cross-sectional respiratory morbidity data. Methods: Chronic respiratory morbidity data within the cohorts were analysed at 5-year intervals (first recorded data from 1986). Based on age at the time of exposure, subjects were stratified into four age groups: children (aged <10 years), teenagers (aged ≥10 to <20 years), younger adults (aged ≥20 to <40 years) and older adults (aged ≥40 years). Results: During the first decade, after exposure to the toxic gases, chronic respiratory morbidity in children and teenagers was high (up to 9.1%), which declined thereafter. Progressively increasing chronic respiratory morbidity was observed in both the younger and older adult age groups within all cohorts during the initial 5–10 years after exposure. Respiratory morbidity in both the younger and older adult age groups remained high for 15–20 years and thereafter recorded a declining trend. The highest respiratory morbidity observed during this study in the younger and older adult age groups was 38.6% and 59.5%, respectively; these values were both recorded in the severely exposed cohort. Conclusions: Exposure to toxic gases released during the Bhopal gas disaster has resulted in chronic respiratory morbidity of the exposed population; this morbidity has continued over decades. The age of the individuals at the time of exposure and exposure severity were crucial determinants of the long-term trend of respiratory morbidity. Highlights: Individuals, from neonates to the elderly, were exposed to toxic gases during the Bhopal gas disaster. Exposed and unexposed cohorts were assembled to assess the health effects. The long-term trend of chronic respiratory morbidity of the cohorts was analysed. Chronic respiratory morbidity of exposed cohorts continued over decades. Exposure severities and age at the time of exposure influenced the trends in respiratory morbidity.